TANTANGAN DAN PELUANG UMKM FASHION PASCA PANDEMI DI KAWASAN UNIVERSITAS JAMBI MENDALO - Ashari, Adelia; Amelia; Aulia, Putri; Tiarmasari, Dwi; Rifki, Ahmad (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the challenges and opportunities of fashion MSMEs in the post-pandemic period around the Universitas Jambi Mendalo area using a qualitative approach with a case study method. The findings show that fashion MSMEs continue to face various challenges, such as increasing business competition, rising capital costs, stock management complexity, and limited digital literacy in utilizing social media and online selling platforms. The rapidly changing behavior of students who constantly follow fashion trends also demands higher adaptability from business owners. Nevertheless, significant opportunities remain through the resurgence of campus activities, strong student interest in fast fashion, the use of e-commerce platforms, and the enhancement of in-store shopping experiences. This research highlights that adaptability, digital marketing innovation, and responsive business management are crucial factors for the sustainability of fashion MSMEs in the post-pandemic era.